2006
DOI: 10.1038/sj.npp.1301239
|View full text |Cite
|
Sign up to set email alerts
|

The Orexin-1 Receptor Antagonist SB-334867 Blocks the Effects of Antipsychotics on the Activity of A9 and A10 Dopamine Neurons: Implications for Antipsychotic Therapy

Abstract: Antipsychotic drugs alter the activity of dopamine neurons in the ventral tegmental area (A10) and substantia nigra pars compacta (A9). As there is a dense projection of orexin neurons from the lateral hypothalamus to A10 dopaminergic neurons, and some antipsychotics have been shown to increase the expression of c-fos in orexin-containing cells in the hypothalamus, we hypothesized that stimulation of orexin receptors plays a role in the effects of antipsychotics on the activity of A9 and A10 dopamine cells. Si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
33
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(34 citation statements)
references
References 37 publications
1
33
0
Order By: Relevance
“…Orexin containing neurons are inactive in sleep and maximally active in waking states characterized by exploratory activity (Lee et al, 2005;Mileykovskiy et al, 2005). Recently, the importance of this endogenous system for sleep cycle regulation was demonstrated by the use of the selective orexin receptor antagonists, including ACT-078573 (Actelion Pharmaceuticals), in rodents, dogs, and man (Smart et al, 2001;Soffin et al, 2002;Brisbare-Roch et al, 2007;Rasmussen et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Orexin containing neurons are inactive in sleep and maximally active in waking states characterized by exploratory activity (Lee et al, 2005;Mileykovskiy et al, 2005). Recently, the importance of this endogenous system for sleep cycle regulation was demonstrated by the use of the selective orexin receptor antagonists, including ACT-078573 (Actelion Pharmaceuticals), in rodents, dogs, and man (Smart et al, 2001;Soffin et al, 2002;Brisbare-Roch et al, 2007;Rasmussen et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The coordination environment around the aluminium centre in Al(OPr i ) 3 can be modified by the reaction of aluminium isopropoxide with the Schiff bases which provide useful steric and electronic properties (Atwood and Harvey, 2001) essential for the reactivity and fine tuning of structure. On the basis of their differences of response in fluorescence emission (Jeanson and Bereau, 2006), 2-(o-hydroxyphenyl)-benzoxazole, their metal complexes (Dubey et al, 2006), were potentially used as cytotoxic agents (Rodriguez et al, 1999;Davison and Corey, 2003;Don et al, 2005), cathapsin S inhibitors (Tully et al, 2006), HIV reverse transcriptase inhibitors (Grobler et al, 2007), estrogen receptor antagonists (Leventhal et al, 2006), selective peroxisome proliferate, activated receptor antagonists (Nishiu et al, 2006), anticancer agents (Easmon et al, 2006), orexin-1 receptor antagonists (Rasmussen et al, 2007). They have also found application as herbicide and as fluorescent whiting agent dyes (Leaver and Milligan, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5] Recently, a survey showed that only 5% of all reactions achieved in the process research groups of three major pharmaceutical companies involve construction of a heteroaromatic rings. 6 Therefore, the development of new methods for the synthesis of nitrogen-containing heterocycles is still a focus of intense and continuing interest in the organic chemistry, as well as in pharmaceutical and agrochemical chemistry.…”
Section: Introductionmentioning
confidence: 99%